Multiple sclerosis and the accumulation of iron in the Basal Ganglia: quantitative assessment of brain iron using MRI t(2) relaxometry - Burgetova, A; Seidl, Z; Krasensky, J; Horakova, D; Vaneckova, M (European neurology, 2010)
The aim of this work was to quantify the accumulation of iron in the basal ganglia in multiple sclerosis (MS) patients and in a control group, and to investigate the relationship between iron accumulation and other parameters assessed in MS, i.e. lesion load (LL) and brain parenchymal fraction (BPF). Magnetic resonance imaging T(2) relaxometry was used for the measurement. 970 patients with clinically definite MS and 117 controls were examined. Patients were divided into three subgroups according to LL and BPF. This work provides quantitative evidence of increased iron accumulation in the basal ganglia in MS patients in comparison to healthy controls. We also found that in the subgroup with small LL value, iron accumulation is higher than in the subgroup with large LL value. The hypothesis of a neurodegenerative component of MS is supported by the changes in iron content in the brain.
Keywords: Young Adult; Male; magnetická rezonanční tomografie; mladý dospělý; bazální ganglia; Multiple Sclerosis; Adolescent; železo; Child; dítě; Adult; Aged; dospělí; mužské pohlaví; senioři; mladiství; lidé; ženské pohlaví; Iron; Basal Ganglia; Humans; mozek - chemie; Brain Chemistry; Magnetic Resonance Imaging; Female; lidé středního věku; roztroušená skleróza; Middle Aged